Breast Cancer Knowledge and Practice among Saudi Arabia Women with and Without Positive Family History: A Cross Sectional Study: Life Sciences-Medical Science - Dayan, Noura Al- (International Journal of Life Science and Pharma Research, 2021)
Knowledge of association between breast cancer and risk factors of family history can help change the health behaviour. To reduce risk factors associated with breast cancer among young women in Saudi Arabia, it is necessary to understand the degree of risk perception and socio-economic differences. A cross-sectional study of 253 Saudi women aged 25-64 years investigated the awareness of risk factors (positive family history) for breast cancer. Standard self-administered questionnaire, screening practices including breast self-examination (BSE), clinical breast examination (CBE), and mammography were included in the data collection and analysed through PRISM (version 8.4.2.) for individuals with and without a positive family history. Prevalence of positive family history and non-family history was 75/253 (30%), and 178/253 (70%) respectively. The mean age of women with a positive family history (FH+) was 47.1 years and without a positive family history (FH-) was 43.4 years. The results showed that both groups were low in practicing BSE (FH+ 23% and FH- 13%) once a month. The BSE knowledge assessment showed 77% in FH+ women whereas the knowledge of CBE and mammography in FH+ women were 75 % and 76% respectively, and 83% and 56% respectively in FH+ women. Awareness of family history as a risk factor was greater in FH+ women compared to FH- women. The women with lower education and low income have less knowledge about breast cancer screening behaviour and FH+ as a risk factor were identified. The results indicated limited knowledge of risk factors and inadequate breast cancer screening of FH+ women. Poor knowledge and practice of breast screening can contribute to late-stage breast cancer disease. Understanding the strengths and importance of the relationship between breast screening activity and its risk factors is essential to the emerging and more tailored promotion of breast health.